Ethnobotanical study of medicinal plants used by Tai Yai in Northern Thailand - Khuankaew S. (2014)
Ethnopharmacological relevance We studied traditional knowledge of medicinal plants used by Tai Yai people in Northern Thailand. We documented traditional medical practices and determined importance among the Tai Yai. This paper reports on knowledge in usage of medicinal plants of the Tai Yai people in Northern Thailand. Materials and methods Interviews were conducted in 4 Tai Yai villages in Mae Hong Son and Chiang Mai provinces whose inhabitants immigrated from Myanmar at different times. Discussions and interviews were held with 126 key-informants (56 males and 70 females) ranging in age from 16 to 80 years in three age groups (age 16-40, 41-60, and 61-80). We calculated the informant consensus factor (ICF) for use category, use value index (UV) for use report of plant. We tested differences between the knowledge of different age groups and locations using principal component analysis (PCA). Results These Tai Yai people used of 141 medicinal plants belonging to 59 families. Of the medicinal plant species, the highest percentage was in the family Euphorbiaceae: Croton acutifolius and Croton roxburghii. The highest number of Informant consensus factor was for metabolic system disorders. Overall, Tai Yai people use medicinal plants to cure many sicknesses such as hypertension, lumbago, wounds, puerperium, kidney disorders, kidney stones, coughs, fevers, hemorrhoids, flatulence and malaria. There were no significant differences in knowledge of plants usage among villages of different ages. In addition, the knowledge of the plants was not significantly different between men and women. However, we found that the younger had less experience with and knowledge of medicinal plants than older people. Conclusions The result indicates loss of accumulated knowledge of medicinal plants and traditional use. Although, the medicinal plant knowledge was passed from one generation to the next by word of mouth, the detailed documentation of medicinal plants and their use may effectively prevent the knowledge-loss through time. © 2013 Elsevier Ireland Ltd.